Prevention and Management of Malaria in Children using a School-Based Program Model - Dorcus Nanvuma; Innocent Besigye; Anna Kabona; Patricia Turimumahoro; Maria Nakitende; Andrew John Macnab (Yayasan Aliansi Cendekiawan Indonesia Thailand (Indonesian Scholars' Alliance), 2026)
Malaria continues to be a major cause of mortality and long-term neurologic handicap globally; the burden of disease is particularly high among children. Those living in rural and poorly resourced areas of the world are the most severely affected, in large part because of inequities in health care for malaria that impact children. School-aged children are a subset of the at risk population who are particularly vulnerable to the adverse consequences of delayed diagnosis, sub-optimal care and repeated infection; both the short and long-term neurologic effects that can result are recognized to compromise the learning ability of affected children. Because of this, schools are a logical and appropriate venue for focusing the fight against malaria. This photo essay illustrates how an effective intervention in rural African schools combines the parallel implementation of a prevention strategy based on the promotion of bed net use by pupils, with a teacher-driven strategy to diagnose and treat malaria through the use of rapid diagnostic testing and artemisinin combination therapy. Strategies such as this reduce inequities in care and offer a way to reduce morbidity from malaria; this in turn gives school children a greater chance of achieving their academic potential by avoiding both absence from school and the long term effects that malaria can have on their ability to learn.